Strategi Pembelajaran Aktif Tipe Team Quiz Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas X SMK Negeri 1 Raya Kabupaten Simalungun Tahun Pembelajaran 2023/2024 - Ernauli Maharani Maarbun; Raikhapoor Raikhapoor; Tianggur Medi Napitupulu (Universitas Maritim AMNI Semarang, 2024)
The research aims to determine the positive and significant influence of the team quiz type active learning strategy on the active learning of Christian Religious Education and Character Education of class The research hypothesis is that there is a positive and significant influence of the team quiz type active learning strategy on the active learning of Christian Religious Education and Characteristics of class Descriptive and inferential quantitative research methods. The population of all class X students at SMK Negeri 1 Raya Simalungun Regency for the 2023/2024 academic year who are Protestant Christians is 159 people. The sample was random (random sampling), namely 40% of the total population minus 30 questionnaire test respondents, namely 40% x 129 people = 52 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value rcount=0.555>rtabel=0.297 and tcount=4.718>ttable=2.000 shows that there is a positive and significant relationship between the team quiz type active learning strategy and students' active learning in Christian Religious Education and Character. b) Regression equation. c) The determination test shows that the magnitude of the effect is 30.80%. d) Hypothesis testing obtained Fcount=22.284>Ftable=3.15 then H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the active learning strategy of the team quiz type on the active learning of Christian Religious Education and Characteristics of class